انتشار أعراض اضطرابات القلق لدى الأطفال وعلاقتها ببعض المتغيرات دراسة على عينتين من الأطفال في عامي 2010 و 2014 - عز, إيمان; البعيني, خزامة (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research aims to know the proportions of the spread of the symptoms of anxiety disorders in children, and differences depending on the variables:( the application years 2010 and 2014, and Gender, and child arrangement in family),among a samples of children (8-13) years old enrolled in the primary schools in Al-Sweida city , n= 596 in 2010 , n = 339 in 2014. The results showed: - decrease in the symptoms of panic disorder and social phobia and obsessive-compulsive, and higher prevalence of symptoms of generalized/Overanxious Disorder of Childhood, separation anxiety , fear of physical harm, in a sample 2010 compared to 2014. - The existence of differences in the order among anxiety symptoms, and the obsessive Obsessive-Compulsive Disorder symptoms are the most prevalent among a sample of 2010 and 2014.- There are statistically significant differences in the appearance of symptoms anxiety disorders patterns separation anxiety, and fear of physical harm according to year application variable, and for the year 2014 sample . - There are significant differences in the appearance of symptoms generalized anxiety disorder, separation anxiety, social phobia, fear of physical harm, generalized anxiety/Overanxious Disorder of Childhood) according to gender variable, and for the female sample. يهدف هذا البحث إلى معرفة نسب انتشار أعراض اضطرابات القلق لدى الأطفال، والفروق تبعاً لمتغيرات: (عام التطبيق2010و2014، والجنس، وترتيب الطفل في الأسرة). لدى عينة من الأطفال بعمر 8 -13 سنة الملتحقين بمرحلة التعليم الأساسي في مدينة السويداء، بلغ عددها 549 لعام 2010 و 386 لعام 2014. وقد أظهرت النتائج :- انخفاضاً في انتشار أعراض اضطرابات الهلع و الرهاب الاجتماعي والوسواس، وارتفاعاً في نسبة انتشار أعراض القلق المعمم /فرط القلق، قلق الانفصال، الخوف من الأذى الجسدي لدى عينة 2014 مقارنه بعينه 2010.- وجود فروق ذات دلالة إحصائية في ترتيب أعراض القلق، وأعراض الوسواس القسري هي الأكثر انتشاراً لدى عينة عامي 2010 و2014. - وجود فروق ذات دلالة إحصائية في ظهور أعراض اضطرابات( قلق الانفصال، والخوف من الأذى الجسدي) لدى العينة تبعاً لمتغير عام التطبيق لصالح عينة العام 2014. - وجود فروق ذات دلالة إحصائية في ظهور أعراض اضطراب القلق العام، وقلق الانفصال، والرهاب الاجتماعي، والمخاوف الأذى الجسدي، القلق المعمم/فرط القلق) لدى العينة تبعاً لمتغير الجنس لصاح الإناث.